THE FATIGUE LIFE MODEL OF HONEYCOMB SANDWICH STRUCTURE - XU DiFeng; YAO WeiXing (Jixie qiangdu)
Among the fatigue life models of honeycomb sandwich structures,the most researched is the S-N curve model.This paper classifies and summarizes the commonly used forms of honeycomb sandwich structures’ S-N curve model. At the same time,the fatigue tests data of honeycomb sandwich structure is collected and normalized according to the relevant mechanical principles,and some general results were obtained. Based on the material properties of the honeycomb core,several influence factors on the fatigue performance of the structure are discussed.